A dataset of cassava whitefly count images - Nakatumba-Nabende, Joyce; Tusubira, Jeremy Francis; Babirye, Claire; Nsumba, Solomon; Omongo Abu, Christopher (Data in Brief, 2022)
Whiteflies are insect vectors that affect a variety of plants such as tomatoes, cabbages, sweet potatoes, eggplants, and cassava. In Uganda, whiteflies are a major contributor to the spread of Cassava Brown Streak Disease (CBSD). By suckling on infected cassava plants, whiteflies can potentially transfer the Cassava Brown Streak Virus that causes CBSD to unin- fected clean plants nearby when they migrate. When they attack the cassava plants in large numbers, whiteflies can also cause significant physical damage through suckling. This eventually can lead to leaf loss or plant death. Whiteflies also excrete “honeydew”, which harbors a fungus known as “sooty mold”that covers the leaves, limiting access to sun- light which in turn affects plant food production. As part of their work, the cassava breeders often conduct studies to as- sess the population of whiteflies in cassava fields through a manual process of visual inspection which can be arduous and time-consuming. This paper presents a cassava whitefly dataset that has been curated to enable researchers to build solutions for the automation of the count and detection of whiteflies. The dataset contains 3,0 0 0 images captured in a whitefly trial site in Uganda. It depicts different variations of whitefly infestation from low to high infestation. This data has already been used to provide a proof-of-concept solution for whitefly counting based on Machine Learning approaches.
Keywords: Cassava; Whitefly; Whitefly count; CBSD